2018
DOI: 10.1002/bdr2.1388
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of cerebellar hypoplasia in the National Birth Defects Prevention Study

Abstract: Although unadjusted, our findings from a large, population-based study can contribute to new hypotheses regarding the etiology of cerebellar hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Cerebellar malformations, including Dandy-Walker malformation (DWM) and several cerebellar hypoplasia (CBLH) subtypes, are among the most common malformations recognized in utero, though their prevalence is unknown. 1 They have proven difficult to study due to incon-sistent classification, largely unknown pathogenesis, and diverse developmental outcomes that may include childhood epilepsy, intellectual disability (ID), cerebral palsy, autism, and other neuropsychiatric disorders. 2,3 Pathogenic variants in only a few genes have been implicated in CBLH or DWM.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellar malformations, including Dandy-Walker malformation (DWM) and several cerebellar hypoplasia (CBLH) subtypes, are among the most common malformations recognized in utero, though their prevalence is unknown. 1 They have proven difficult to study due to incon-sistent classification, largely unknown pathogenesis, and diverse developmental outcomes that may include childhood epilepsy, intellectual disability (ID), cerebral palsy, autism, and other neuropsychiatric disorders. 2,3 Pathogenic variants in only a few genes have been implicated in CBLH or DWM.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of technology and the use of fetal MRI, the detection rate of cerebellar hypoplasia has increased (23). Also, In the study of Howley MM et al (24), it was shown that only 26.4% of cerebellar hypoplasia cases had isolated cerebellar hypoplasia and that other central nervous system malformations were accompanied in the majority of cases. In our study, it was observed that 19.0% of cerebellar hypoplasia/agenesia cases had accompanying multiple anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…This long period of development(protracted development) makes the cerebellum vulnerable to common developmental disorders such as Dandy-Walker malformations and pontocerebellar hypoplasia (Ten Donkelaar and Lammens 2009).There are four important phases of cerebellar development namely, cerebellar territory characterization; the formation of ventricular zone and rhombic lip forming Purkinje cells, deep cerebellar nucleus and granule cells; the migration of granule layer from external to internal and lastly the cerebellar circuitry formation (ten Donkelaar et al 2003).Apart from the formation of cerebellar hemispheres, the cerebellar vermis, a small, hindbrain structure develop from the rostral segments of the rhombencephalon in early gestation (Martinez et al 2013, Millen andGleeson 2008).The cerebellum contribute to both motor and non-motor functions such as movement, proprioception, and cognition (Basson and Wingate 2013, Koziol et al 2014, Ben-Yehudah, Guediche, and Fiez 2007. Cerebellar malformations are common (Santoro et al 2019, Howley et al 2018 and have long term consequences in children (Pinchefsky et al 2019, Abel andTahir 2019),therefore frontiers in obstetric and radiological societies emphasize the important for routine screening of the cerebellum and vermis in utero (Haratz et al 2019, Quarello et al 2014. Early detection (prenatal diagnosis of the cerebellar abnormality is essential and have some prognostic impacts (Patek et al 2012, Gandolfi Colleoni et al 2012, Wuest et al 2017.Obstetric ultrasound has been a routine diagnostic tools in evaluation of fetal well-being in utero (Whitworth, Bricker, andMullan 2015, Henrichs et al 2019), however, the fetal cerebellar structures such as the vermis, being small in size and deep in skull base, the routine axial sonography may not suffice to depict the subtle changes during cerebellar development (Yang et al 2012, Pugash et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum contribute to both motor and non-motor functions such as movement, proprioception, and cognition(Basson and Wingate 2013, Koziol et al 2014, Ben-Yehudah, Guediche, and Fiez 2007). Cerebellar malformations are common (Santoro et al 2019, Howley et al 2018) and have long term consequences in children(Pinchefsky et al 2019, Abel and Tahir 2019),therefore frontiers in obstetric and radiological societies emphasize the important for routine screening of the cerebellum and vermis in utero(Haratz et al 2019, Quarello et al 2014). Early detection (prenatal diagnosis of the cerebellar abnormality is essential and have some prognostic impacts (Patek et al 2012, Gandolfi Colleoni et al 2012, Wuest et al 2017).…”
Section: Introductionmentioning
confidence: 99%